DEVELOPMENT OF SALES APPLICATION OF PREPAID ELECTRICITY VOUCHER BASED ON ANFROID PLATFORM USING QUICK RESPONSE CODE (QR CODE) - Ricky Akbar; Husnil Kamil (Universitas Ahmad Dahlan, 2017)
Perusahaan Listrik Negara (PLN) has implemented a smart electricity system or prepaid electricity. The customers pay the electricity voucher first before use the electricity. The token contained in electricity voucher that has been purchased by the customer is inserted into the Meter Prabayar (MPB) installed in the location of customers. When a customer purchases a voucher, it will get a receipt that contains all of the customer's identity and the 20-digit of voucher code (token) to be entered into MPB as a substitute for electrical energy credit. Receipts obtained by the customer is certainly vulnerable to loss, or hijacked by unresponsible parties. In this study, authors designed and develop an android based application by utilizing QR code technology as a replacement for the receipt of prepaid electricity credit which contains the identity of the customer and the 20-digit voucher code. The application is developed by implemented waterfall methodology. The implementation process of the waterfall methods used, are (1) analysis of functional requirement of the system by conducting a preliminary study and data collection based on field studies and literature, (2) system design by using UML diagrams and Business Process Model Notation (BPMN) and Entity Relationship diagram (ERD), (3) design implementation by using OOP (Object Oriented programming) technique. Web application is developed by using laravel PHP framework and database MySQL while mobile application is developed by using B4A (4) developed system is tested by using blackbox method testing. Final result of this research is a Web and mobile applications for the sale of electricityvoucher by QR Code technology.